Pengaruh Program Pendidikan Jasmani Terhadap Kebugaran Fisik Siswa Sekolah Dasar Negeri 064966 Medan - Fajar Siddik; Nazwa Dewi Tianda; Safana Nur Risky; Riani Tazkia Hadi; Lidwina Roulina Turnip; Delfi Wulandari (Student Scientific Creativity Journal, 2024)
Physical education plays an important role in improving the fitness and health of the younger generation, especially at primary school level. This study aims to analyze the effect of physical education programs on the physical fitness of elementary school students. With a qualitative approach, this research collects data through interviews and observations to understand the relationship between physical education programs and students’ physical fitness. The research results show that the level of physical fitness of students at SD Negeri 064966 is still less than optimal, mainly due to lack of physical activity. The physical fitness of male students is better than that of female students, and fitness levels increase with grade level. Physical education programs are proven to have many benefits, including improving physical health, motor skills, mental well-being, social interaction, preventing obesity, developing healthy habits, and improving concentration and academic achievement. In conclusion, a structured physical education program can significantly improve students’ physical fitness and quality of life, so it needs to continue to be developed and implemented effectively in elementary schools.